Estimation of Renal Resistive Index as an Early Marker of Diabetic Nephropathy - Kushal Markanday; Periyapattana Gopinath Kumar; Buvana Radhakrishnan; Sheeba Rafath (APIK Journal of Internal Medicine, 2025)
Background: Diabetic nephropathy (DN) occurs due to angiopathy of glomerular capillaries, which alters the compliance and resistance of the vessel wall. This can be measured with the renal resistive index (RI) using renal Doppler, indicating disease progression. Aims and Objectives: This study aimed to assess the utility of RI in type 2 diabetes mellitus and to study the association between RI and DN and other complications. Materials and Methods: One hundred diabetic patients, 50 each with and without nephropathy, alongside 50 nondiabetics (controls) were included. All 100 cases were assessed for RI, glycemic control, and diabetic complications. RI was also evaluated for the 50 nondiabetic controls. Results: RI was higher in patients with macroalbuminuria (0.661 ± 0.04) compared to patients without microalbuminuria (0.58 ± 0.05), and there was a progressive increase in RI with the progression of diabetic renal disease; hence, it had an inverse relation with estimated glomerular filtration rate eGFR. Conclusions: Albuminuria and eGFR influence RI, and it rises among people with diabetes (with or without DN) even before the onset of raised creatinine levels. Hence, Baseline estimation of the RI as a marker of intra-renal vascular resistance can be an additional diagnostic tool for diabetic nephropathy.